New Model of Linear Induction Drive - Rinkevičienė, R.; Petrovas, A. (Elektronika ir Elektrotechnika, 2004)
The article deals with mathematical model of linear induction drive and a developed Simulink model based on that. Developed model gives possibility to investigate transients of electric drives with rotating and linear induction motors at balanced and unbalanced supply voltage and at equal or distinct parameters of phase windings during starting process of motor with load or no-load. Derived formula to calculate developed force or torque is presented. Model of linear induction motor is developed as entity of objects corresponding to proper parts of motor: model of winding object, model of mechanical part object and model of electromechanical part object. Analysed dependencies between mechanical quantities in both rotating and linear motor used to develop model, Calculated results: force developed by linear induction motor, speed, currents of all phase windings of inductor and secondary and other parameters are obtained in form of graphs. Ill. 5, bibl. 13 ( in English; summaries in Lithuanian, English and Russian).